The Stratified Superconductivity in Ba0.6K0.4BiO3 Single Crystal: Direct Measurement of Energy Gap between Homo-, and Inhomogeneous States. (2nd March 2014) - Zherikhina, L. N.; Tskhovrebov, A. M.; Klinkova, L. A.; Balaev, D. A.; Popkov, S. I.; Shaikhutdinov, K. A.; Velikanov, D. A.
Abstract : The existence of space inhomogeneous superconductor insulator state (SISIS) found out earlier in polycrystalline samples of high-T C systemBa 0.6 K 0.4 BiO 3 (T C ≈ 30 K) is confirmed onBa 0.6 K 0.4 BiO 3 single crystal. AtT * (T * < T C, T * ≈ 17 K) the transition from the homogeneous superconducting state into the SISIS occurs. SISIS is characterized by the appearance of two gaps on the Fermi surface, semi- and superconducting, which are modulated in space in antiphase, the electric transport between superconducting regions being carried out due to Josephson tunneling. Thus the whole sample becomes a multiple Josephson system. NonlinearI - V curves are observed onBa 0.6 K 0.4 BiO 3 single crystal at temperatures belowT * . Dependence ofI - V curves on temperature and magnetic field, typical to a Josephson system, was found out. Besides, a step-like peculiarity at the values of voltage of the order of one and two superconducting gaps shows up. These peculiarities are suppressed by magnetic field much earlier than critical current. The new data firstly correlate with the model of SISIS and secondly permit for the first time to determining directly the energy gap between homogeneous and stratified superconductor states.